Symposium on "The big inquiry" Tuesday, 25 May, 1982, Institution of Civil Engineers, Great George Street, London SW1. (Thomas Telford, 1982)
Papers cover new procedures for public inquiries into major public projects; a view of The Big Inquiry from the planning bar; reflections on the NCB experience; and views of environmental issues.